Analisis Faktor-Faktor yang Mempengarugi Intensi Muzaki Membayar Zakat: Sebuah Survey pada Masyarakat Kota Bekasi - Purnama Putra (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2016)
The purposes of the research are: (1) to find out the factors influencing the intention of muzaki to pay zakah; (2) to find out to what extent that the factors influence the intention of muzaki to pay zakah; (3) to find out which factor among others that dominantly influences the intention of muzaki to pay zakah. The method employed in the research is quantitative method with the approach of multiple regression processed by using software SPSS 20,0. The data was collected from the questionnaires distributed to some muzaki in four different districts of Bekasi (Rawalumbu, Bekasi Timur, Bekasi Selatan and Mustika jaya). The sample was chosen purposively with the number of 30 people to test the validity and the reliability of the instruments and 100 people were contributed as the respondents. The factors influencing the intention of muzaki to pay zakah in Bekasi are: attitude, subjective norms, and the control of behavior. The three factors gave significant influence altogether to the variable of muzaki’s intention to pay zakah. The amount of attitude variable to the intention of muzaki to pay zakah was as much 4.62%, the variable of subjective norm was 2.88%, the variable of behavior control was 8.5%. Therefore, it can be concluded that the most dominant factor influencing the intention of muzaki to pay zakah was the variable of behavior control which reached 8.5%.